Viabilidad de comunidades profesionales de aprendizaje en sistemas educativos de bajo desempeño - Morales-Inga, Sergio (2020)
Professional learning communities (PLCs) are one of the most significant school performance strategies. Yet, most of the schools that have applied them belong to high-performance educational systems, such as those of Japan, South Korea, Finland or Singapore, leaving out the educational reality of Latin America. Through an exploratory study based on ethnographic observation and semi-structured interviews, this research links theory to practice to discuss the applicability of PLC to public schools in low-performance educational systems. In conclusion, it was found that the main components of PLCs (flexible organizational structures, distributed leadership, shared values, and collaborative school cultures) are present but precarious and do not support the implementation of the strategy.